2007
DOI: 10.2307/20445427
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Self and Other in the Prisoner’s Dilemma: Outcome Bias and Evidential Reasoning

Abstract: In the prisoner’s dilemma, self-interest clashes with collective interest. The way players resolve this conflict affects how others view them. Cooperators are seen as more moral than defectors, and, when there is no information about the other player’s choice, cooperators and defectors are seen as equally competent. However, players who are defected against are seen as less competent, especially if they themselves cooperated (Experiments 1 and 2). Similarly, cooperators see themselves as more moral, but not as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 51 publications
7
40
1
2
Order By: Relevance
“…Individual differences in the strength of projection predict cooperation in prisoner dilemmas, voting intentions, and intentions to contribute to a public good (Acevedo & Krueger, 2004;Krueger & Acevedo, 2007. As in all social dilemmas, in the PD a person is faced with a situation of social interdependence.…”
Section: The Social Projection-cooperation Linkmentioning
confidence: 99%
“…Individual differences in the strength of projection predict cooperation in prisoner dilemmas, voting intentions, and intentions to contribute to a public good (Acevedo & Krueger, 2004;Krueger & Acevedo, 2007. As in all social dilemmas, in the PD a person is faced with a situation of social interdependence.…”
Section: The Social Projection-cooperation Linkmentioning
confidence: 99%
“…The Cognitive Approach to Decision Making Studies have found that temporal and contextual biases frequently affect decision making, leading to outcomes not predicted by rational choice models of utility maximization (Kahneman 2012;Krueger and Acevedo 2007;Budescu and Maciejovsky 2005;Stein and Welch 1997;Quattrone and Tversky 1988;Kahneman andTversky 1979 and. In response to these findings, cognitive psychologists have concentrated on "identifying and categorizing the filters through which people process information and the simplifying mechanisms they employ to help them make sense of the world" (Stein and Welch 1997:53).…”
Section: Simulationsmentioning
confidence: 99%
“…5(c) have all resorted to essential changes in the specification of the game, introducing either repetitions (e.g., Aumann & Sorin, 1989), a "cheap talk" stage during which players can make costless announcements before choosing their strategies (e.g., Farrell, 1988), modifications of the assumption that players know that they choose their strategies independently (e.g., Colman & Bacharach, 1997;Krueger, 2008;Krueger & Acevedo, 2007), or special modes of reasoning (Bacharach, 1999(Bacharach, , 2006Sugden, 1993Sugden, , 2005.…”
Section: Berge Equilibrium Coordination and Payoff Dominancementioning
confidence: 99%